Digital Support for Oral Performance: The Effect of Fondi Application on Speaking Confidence - Tika; Kadaruddin; Karimuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the effectiveness of the Fondi app in boosting Indonesian EFL students’ speaking self-confidence. A quasi-experimental design was conducted with 60 eleventh-grade students from SMAN 1 Bombana, divided equally into experimental and control groups. The intervention lasted four sessions (90 minutes each) over four weeks. Data was compiled using a 30-item self-confidence questionnaire and a speaking performance test. When compared to the control group, statistical analysis showed that the experimental group had significantly improved (p = 0.001, Cohen’s d = 2.98, 95% CI [10.3, 14.8]). The experimental group achieved a 0.85–0.89 gain across five indicators of speaking confidence, while the control group showed only minimal progress (0.18–0.26). These findings support Bandura’s self-efficacy theory, demonstrating that digital tools like Fondi can provide mastery experiences and supportive environments to strengthen learners’ affective readiness. The study concludes that Fondi is an effective digital support for oral performance, though further research with delayed post-tests and larger samples is recommended.